PENGEMBANGAN DESA WISATA ALAM DAN BUDAYA MELALUI PENDEKATAN PENTA-HELIX - Humam Santosa Utomo; Hendro Widjanarko; Suratna Suratna (PUBLIC CORNER, 2022)
Wukirsari is one of the natural and cultural tourism villages that has developed in Bantul, Yogyakarta. The uniqueness of natural and culture in Wukirsari is offered to domestic and foreign tourists. This study aims to determine the role of each stakeholder in the development of a cultural tourism village in Wukirsari. The results of this study are expected to be best practice for cultural tourism village managers in other places. Sources of data were collected using in-depth interviews and focus group discussions involving all stakeholders. Qualitative data were analyzed to determine the role of each stakeholder. The results of this study indicate that the community, government, universities, the business world, and the media play an active and collegial role in developing Wukirsari as a cultural tourism village. Keywords: natural and Cultural tourism village, wukirsari, stakeholders